Pathologic Outcomes of Laparoscopic vs Open Mesorectal Excision for Rectal Cancer - Adrian, Adrian; Fitriana, Fitriana (International Medical Journal Corp. Ltd, 2024)
Background: The exploration of surgical approaches for rectal cancer has garnered significant attention in recent years, particularly in evaluating the pathologic outcomes associated with laparoscopic versus open mesorectal excision. Literature Review: The literature review on the pathologic outcomes of laparoscopic versus open mesorectal excision for rectal cancer reveals a nuanced understanding of the comparative effectiveness of these surgical approaches. The introduction establishes the significance of complete mesorectal excision (TME) as a critical factor in improving patient outcomes, with both laparoscopic and open techniques being scrutinized for their oncological safety and efficacy. Conclusion: In conclusion, the literature presents a complex landscape regarding the pathologic outcomes of laparoscopic versus open mesorectal excision for rectal cancer. While laparoscopic techniques show promise in enhancing short-term recovery and maintaining oncological adequacy, the ongoing concerns about long-term outcomes and the quality of surgical margins necessitate further investigation. The evidence suggests that both approaches have their merits, but careful consideration and adherence to oncological principles are essential to optimize patient outcomes.